Surgical treatment and analysis of canine penetrating corneal trauma due to plant-derived foreign bodies: a case report - Shi, Rui (Slovenian veterinary research, 2025)
The objective of this study is to present a case of canine penetrating corneal trauma caused by plant-derived foreign bodies, successfully treated with keratotomy. A 2-yearold female Border Collie presented with two corneal foreign bodies, conjunctival congestion, blepharospasm, and a small amount of serous discharge in the left eye. Keratotomy was performed to remove the foreign bodies from the cornea. During the procedure, one foreign body was observed to have penetrated the anterior chamber. Following removal, the anterior chamber was irrigated, and the cornea was sutured. Postoperative treatment included both topical and systemic medications. Examination confirmed that the foreign bodies were plant-derived. Postoperative assessments at 2 and 4 weeks showed a reduction in corneal edema, formation of limbal neovascu-larization, decreased conjunctival congestion, resolution of blepharospasm, and ab-sence of ocular discharge. The 5-month postoperative follow-up demonstrated nor-mal corneal clarity and physiological function, a clear anterior chamber, and normal vision. Keratotomy has been demonstrated to be an effective intervention for corneal foreign bodies, allowing thorough removal of fragile and deeply embedded materials. Postoperative medications effectively prevented infections and promoted corneal heal-ing. This case report provides valuable insights into the diagnosis and management of canine penetrating corneal trauma caused by plant-derived foreign bodies.
Keywords: canines; corneal repair; foreign body removal; keratotomy; penetrating corneal trauma; plant-derived foreign body